Precarious Employment: Towards an Improved Understanding of Labour Market Insecurity - Vosko, Leah F. (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
This chapter initiates the conversation between theory, method, evidence, and practice that is the focus of this book. It conceptualizes precarious employment, probes its dynamics in Canada, and identifies avenues for fostering understanding in the service of positive social change by way of several linked arguments set in the three major sections that follow. –Author's introduction
https://www.mqup.ca/precarious-employment-products-9780773529618.php
Keywords: Industrial hygiene; LABOR market; Labor Unions; Labor laws and legislation; Temporary employment